2019
DOI: 10.1177/0886260519860084
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Posttraumatic Stress Disorder Symptomology Among Women Who Have Experienced Sexual Assault in Canada

Abstract: There is a dearth of information about the association of victim-related and assailant-related characteristics and posttraumatic stress disorder (PTSD) among sexually assaulted women. Recently, Statistics Canada included items measuring the possible presence of PTSD symptoms in their 2014 nationally representative General Social Survey on Victimization (GSS-V), for the purpose of improving the understanding of mental health impacts associated with sexual victimization. The present study used the GSS-V to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Sexual violence, defined as unwanted sexual acts against someone (Ulloa et al, 2016), is a global public health and criminal justice problem (Du Mont et al, 2019). Prevalence rates vary considerably across studies with rates ranging from 10.7 to 21.2% for contact-based sexual violence and up to 15.1% for penetrative sexual offenses against children with consistent findings across international studies that girls are at a considerable higher risk of victimization than boys (Tanaka et al, 2017).…”
Section: Introductionmentioning
confidence: 87%
“…Sexual violence, defined as unwanted sexual acts against someone (Ulloa et al, 2016), is a global public health and criminal justice problem (Du Mont et al, 2019). Prevalence rates vary considerably across studies with rates ranging from 10.7 to 21.2% for contact-based sexual violence and up to 15.1% for penetrative sexual offenses against children with consistent findings across international studies that girls are at a considerable higher risk of victimization than boys (Tanaka et al, 2017).…”
Section: Introductionmentioning
confidence: 87%
“…It is, therefore, important to continuously build on evidence-based prevention programs aimed at reducing family violence (Waller, 2011). Future research should explore this complex interplay of the trauma experienced in childhood as a result of experiencing or witnessing victimizations and subsequent victimization in adulthood, as well as how to appropriately respond to the specific needs of this group (Du Mont et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Six studies highlighted how more severe forms of adolescent/adult sexual assault/abuse may be associated with worse mental health outcomes. 47,52,54,69,75 For example, Peter-Hagene and Ullman 54 found that women who had experienced high-violence or alcohol-related sexual assault had more severe PTSD symptoms than women who experienced moderate severity sexual assault. The effects of high-betrayal sexual assault (i.e.…”
Section: Risk and Protective Factorsmentioning
confidence: 99%
“…sexual assault by a close other) was examined in Gomez 75 , who found that individuals who had experienced adolescent high-betrayal adolescent sexual assault, reported greater depersonalisation, which in turn predicted NSSI. Du Mont et al (2019) 47 also examined how relationship to perpetrator affects mental illness symptoms, and found that in a sample of women who had experienced sexual assault, women who knew the perpetrator were more than 3 times more likely to experience PTSS than women who did not know the perpetrator.…”
Section: Risk and Protective Factorsmentioning
confidence: 99%